Onset of age, site and respiratory symptoms are strongly associated with respiratory decline in sporadic amyotrophic lateral sclerosis: a long-term longitudinal study - Gen Sobue; Shin-ichi Terao; Yasunobu Nosaki; Atsunori Murao; Ryota Torii; Nanayo Ogawa; Naofumi Miura; Yousuke Sasaki (BMJ Neurology Open)
Objective The objective of this study is to identify factors influencing progression of respiratory decline from the onset of neurological symptoms to respiratory failure in patients with amyotrophic lateral sclerosis (ALS).Methods In 100 patients with sporadic ALS, %vital capacity (%VC) was continuously measured from the first visit to the respiratory endpoint (REP). Cox proportional hazards model identified factors influencing the duration from onset of ALS to REP (Onset-REP). We performed Kaplan-Meier survival curve analysis for onset-REP according to identified factors.Results Onset sites were the upper limb (U-ALS), lower limb (L-ALS), bulbar paralysis (B-ALS) and respiratory paralysis (R-ALS) in 37, 19, 32 and 12 patients, respectively. Duration from the onset of ALS to the onset of respiratory symptoms (Onset-Rp) and REP (Onset-REP) was 16.1 (SD 12.1) and 24.9 months (SD 14.6), respectively. Multivariate analysis revealed that age at onset, site of onset, Onset-Rp and %VC decline rate significantly influenced Onset-REP duration. Elderly patients had a significantly shorter Onset-REP duration. Onset-REP duration did not significantly differ between patients with U-ALS and L-ALS, but was longer in these patients than in those with B-ALS and R-ALS. Onset-REP duration was positively associated with Onset-Rp duration. The average monthly %VC decline rate was −5.6% (SD 3.3). Age at onset, onset site and Onset-Rp duration significantly influenced the %VC decline rate.Conclusions Our findings revealed strong and independent patient-specific factors that influence the Onset-REP duration and the %VC decline rate in patients with ALS. These could inform future clinical trials and interventions considering the respiratory function and natural history of patients with ALS.